Combination of romidepsin with cyclophosphamide, doxorubicin, vincristine, and prednisone in previously untreated patients with peripheral T-cell lymphoma: a non-randomised, phase 1b/2 study. Issue 4 (April 2015) - Dupuis, Jehan; Morschhauser, Franck; Ghesquières, Hervé; Tilly, Hervé; Casasnovas, Olivier; Thieblemont, Catherine; Ribrag, Vincent; Bossard, Céline; Bras, Fabien Le; Bachy, Emmanuel; Hivert, Bénédicte; Nicolas-Virelizier, Emmanuelle; et al.
Summary: Background: Romidepsin is a histone deacetylase inhibitor approved in the USA for patients with recurrent or refractory peripheral T-cell lymphoma and has shown activity in this setting with mainly haematological and gastrointestinal toxicity. Although it has limited efficacy, cyclophosphamide, doxorubicin, vincristine, and prednisone (CHOP) therapy is widely used for treatment of de-novo peripheral T-cell lymphoma. We aimed to assess the safety, tolerability, and activity of romidepsin combined with CHOP in patients with previously untreated disease. Methods: We enrolled patients aged 18–80 years with histologically proven, previously untreated, peripheral T-cell lymphoma (Eastern Cooperative Oncology Group performance status ≤2) into a dose-escalation (phase 1b) and expansion (phase 2) study at nine Lymphoma Study Association centres in France. In the dose-escalation phase, we allocated consecutive blocks of three participants to receive eight 3 week cycles of CHOP (intravenous cyclophosphamide 750 mg/m 2, doxorubicin 50 mg/m 2, and vincristine 1·4 mg/m 2 [maximum 2 mg] on day 1 and oral prednisone 40 mg/m 2 on days 1–5) in association with varying doses of romidepsin. The starting dose was 10 mg/m 2 intravenously on days 1 and 8 of each cycle, and we used a 3 + 3 design. We assessed dose-limiting toxicities only during the first two cycles. The primary endpoint was to determine the recommended dose for the combination. For the phase 2 study, we aimed to increase the cohort of patients receiving the recommended dose to a total of 25 patients. Patients were assessed for safety outcomes at least twice per cycle according to the Common Terminology Criteria for Adverse Events, version 4.0. Safety analyses included all patients who received at least one dose of romidepsin and CHOP. This trial is registered at the European Clinical Trials Database (EudraCT), number 2010-020962-91 andClinicalTrials.gov, numberNCT01280526 . Findings: Between Jan 13, 2011, and May 21, 2013, we enrolled 37 patients (18 treated in phase 1b and 19 patients in phase 2). Three of six patients initially treated at 10 mg/m 2 had a dose-limiting toxicity. The dose-escalation committee decided to modify the study protocol to redefine dose-limiting toxicities with regard to haematological toxicity. Three patients were treated with 8 mg/m 2 of romidepsin, an additional three at 10 mg/m 2 (one dose-limiting toxicity), and six patients at 12 mg/m 2 (three dose-limiting toxicities). We chose romidepsin 12 mg/m 2 as the recommended dose for phase 2. Of the 37 patients treated, three had early cardiac events (two myocardial infarctions and one acute cardiac failure). No deaths were attributable to toxicity. 25 (68%) of 37 patients had at least one serious adverse event. Overall, the most frequent serious adverse events were febrile neutropenia (five [14%] of 37 patients), physical health deterioration (five [14%]), lung infection (four [11%]), and vomiting (three [8%]). 33 (89%) of patients had grade 3–4 neutropenia, and 29 (78%) had grade 3–4 thrombocytopenia. Interpretation: Romidepsin can be combined with CHOP but this combination should now be tested in comparison to CHOP alone in a randomised trial. Funding: Celgene.